2013
DOI: 10.1542/peds.2012-3588
|View full text |Cite
|
Sign up to set email alerts
|

ADHD and Learning Disabilities in Former Late Preterm Infants: A Population-Based Birth Cohort

Abstract: BACKGROUND AND OBJECTIVE: Previous studies suggest that former late preterm infants are at increased risk for learning and behavioral problems compared with term infants. These studies have primarily used referred clinical samples of children followed only until early school age. Our objective was to determine the cumulative incidence of attention deficit/hyperactivity disorder (ADHD) and learning disabilities (LD) in former late preterm versus term infants in a population-based birth cohort.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 40 publications
1
45
1
4
Order By: Relevance
“…38 Likewise, a United States-based group found similar rates of learning disability and attention deficit/hyperactivity disorder diagnoses in LPIs and FTIs in a white, middle class community without ethnic and racial diversity. 39 Our study cohort has the strengths of being a large nationally representative sample with robust follow-up at kindergarten and data collected from multiple sources including parents, birth certificates, and direct in-home assessments of children. The assessments were conducted by trained assessors with excellent quality control measures.…”
Section: Figurementioning
confidence: 99%
“…38 Likewise, a United States-based group found similar rates of learning disability and attention deficit/hyperactivity disorder diagnoses in LPIs and FTIs in a white, middle class community without ethnic and racial diversity. 39 Our study cohort has the strengths of being a large nationally representative sample with robust follow-up at kindergarten and data collected from multiple sources including parents, birth certificates, and direct in-home assessments of children. The assessments were conducted by trained assessors with excellent quality control measures.…”
Section: Figurementioning
confidence: 99%
“…In assessing performing functions and their relation to language, several studies indicated a positive correlation between attention abnormalities and other performing functions and poorer language performance (22,27) , having also related it to lower gestational age (27) and poorer nonverbal learning (27) . Premature children presented poorer performing functions (22) , although they are not different from full-term infants in terms of attention-deficit and hyperactivity disorder (21) . One study (14) , however, indicates that attention at 18 months predicts language abnormalities at 36 months, ratifying attention span as a precursor of language, although attention is not positively associated with the mother's educational level, as is language in general.…”
Section: Resultsmentioning
confidence: 81%
“…In contrast, two studies (20)(21)(22)(23) found no association of retinopathy of prematurity with language outcomes. However, the study suggests that gestational age, low weight at birth and gender may be more influential in the long term in these children, thus being necessary to monitor this population -as has been observed in other studies reviewed (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) .…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations